LAMA PENGGUNAAN MASKER TIDAK MEMENGARUHI TIMBULNYA JERAWAT PADA PEREMPUAN USIA 15-60 TAHUN - Agatha Ratri Rini Kusrini; Pusparini Pusparini (Jurnal Akta Trimedika, 2024)
Acne is an inflammatory dermatosis of the pilosebaceous follicular unit. Many factors influence the onset of acne, including facial skin hygiene and skin moisture. The use of masks can have an impact on increasing facial skin moisture and pressure on the skin. This study aims to determine relationship between length use of masks and appearance of acne and factor influencing in women age 15-60 years old. A cross sectional design was conducted on respondents with inclusion criteria of women aged as mentioned previously. Data was collected using a google form questionnaire. The relationship between variables were analyzed statistically with Spearman test with p <0,05 and Chi Square test with p <0,05 significantly different. Total of 225 respondents participated in this study. Respondents used masks for 3 hours and more are 190 (84.5%) respondents. Respondents reported the occurrence of acne after using the mask are 143 (63.5%). Statistical analysis did not find a significant relationship between the duration of using a mask and the onset of acne (p=0.391). Factors that showed a significant relationship with the onset of acne were age, menstrual cycle, education level, facial care, and washing face more often. The duration of using a mask is not related to the appearance of acne in women of reproductive age. Factors influencing with the appearance of acne are age, menstrual cycle, education level, facial care, and washing face more often.